LATIHAN EXERCISE WITH GROUPS OF 3 DAN EXERCISE WITH GROUPS OF 4 DAPAT MENIGKATKAN KEMAMPUAN PASSING SEPAK BOLA - Nurhabib, Nova Rizzal; Hulfian, Lalu (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Football is a game that is done by kicking the ball by the player, by kicking the goal and aiming to put the ball into the opponent's goal. Passing is one of the basic techniques that must be mastered by soccer players. The results of observations on the field are still many players who have not done well passing. The formulation of the problem in this research is whether there is an effect of exercies with groups of 3 and exercises with groups of 4, and which exercises have more influence on the passing ability of football on Keluncing FC players in 2020. The purpose of this study is to determine the effect of exercies exercise with groups of 3 with groups of 3 and exercies with groups of 4 to the ability of passing soccer on the Keluncing FC 2020 players. This study uses an action test with a research design that is two group pretest-postest design. The population and sample are all 22 Keluncing FC players. The passing assessment is carried out by holding and kicking the ball alternately between the left foot and right foot for 30 seconds. Data were analyzed using SPSS version 22. Group 1 t-test results obtained significant values (2-tailed) < 0,05 : 0,003 < 0,05 and group 2 significant values (2-tailed) < 0,05: 0,038 < 0,05. Then these results indicate that there are significant differences. Based on the test differences in the average post-test data of groups 1 and 2 obtained a significant value (2-tailed) < 0,05 : 0,026 < 0,05 with a percentage increase in group 1 of 12,93% and group 2 of 3,96%. Based on the results of the analysis it can be concluded that exercising with groups of 3 is more influential than exercising with groups of 4 on the passing ability of the FC Keluncing players in 2020